Virtual Capital? Internet Competence and Political Participation in Denmark - Hoff, Jens (MedieKultur: Journal of media and communication research, 2006)
On the basis of data from a Danish nationwide representative survey, this article demonstrates, firstly, that virtual capital (compentence in using the internet) is a personal resource in its own right, independent of other types of personal resources. Secondly, it is demonstrated that there is a positive correlation between virtual capital and political parti- cipation and political efficacy. Thirdly, the article shows that for persons with a high level of virtual capital, the possession of virtual capital appe- ars to neutralize or overshadow the effect of education on political par- ticipation and political efficacy. The article points to the fact that the In- ternet enlarges the "opportunity structure" for the individual, thereby making it easier to find out about and participate in different activities, among these politics. Finally, the article discusses the question of whether "super-users" might be seen as (a part of) the so-called "creative class".